Debts, Taxation, their Cost, and Social Welfare - Kallianiotis, Ioannis N. (Archives of Business Research, 2014)
The current paper discusses the enormous debts, the current tax system, and the ultimate objective of a nation, which is the social welfare of its citizens. The high taxes reduce the disposable income and make savings negative (dissaving or borrowing). This increases further the debt of individuals and the low taxes on businesses have magnified the budget deficits and the national debt. People are borrowing the present value of their uncertain future wealth and their high debt and low income raise the risk and this high risk premium heighten the interest rate on loans, especially on the usurious credit cards. Government has to increase corporate taxes and reduce the national debt by lowering government expenditures (military expenditures and national defense). The current tax system needs to be changed and an interest rate floor on deposits (savings) and an interest rate ceiling on individuals' loans (borrowings) is necessary to impove social welfare, fairness, and justice in our society. The middle class cannot work only to pay taxes and interest on its debt (redistribution of their wealth to government and banks), due to low disposable income. The disappearing of the middle class will wffect negatively the entire socio-economic structure of the nation and after losing its power, it will start declining, as history has shown to us with so many empires that do not exist anymore. We hope the leaders to regain their power and lead the abandoned people to their ultimate objective, which is their perfection and the nation to its highest social welfare.